الهجرة غير الشرعية وتداعياتها على الأمن الوطني الجزائري - بلحاج سليم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
يحاول الباحث من خلال هذه الدراسة إلقاء الضوء على أحد أخطر التهديدات اللاتماثلية التي تمس الأمن الوطني الجزائري، والمتمثلة في الهجرة غير الشرعية والتي زادت حدتها خلال السنوات الأخيرة، نظرا لتشابك مسبباتها وتنامي تداعياتها، فالانتشار المفزع لهذه الظاهرة أرغم الجزائر على دق ناقوس الخطر، من خلال تصنيف هذه الظاهرة في خانة الجرائم الماسة بأمنها الوطني بمختلف أبعاده، ما يتطلب تبني مقاربة وإستراتيجية شاملة ومتوازنة من أجل إدارة فعالة للحد من تداعياتها. Through this study, the researcher tries to shed light on one of the most serious asymmetric threats affecting Algerian national security, which is represented by illegal immigration, which has increased in intensity in recent years, due to the complexity of its causes and its growing repercussions. The alarming spread of this phenomenon has forced Algeria to ring the alarm, While classifying this phenomenon in the category of crimes affecting its national security in its various dimensions, which requires adopting a comprehensive and balanced approach and strategy in order to effectively manage its consequences.